Economic Content in the Narratives of Władysław I the Elbow-High’s Diplomas – Clichéd Form Records or a Symptom of Awareness of the Medieval Ruler? - Obara-Pawłowska, Anna (Studia Historiae Oeconomicae, 2020)
The article analyzes the economic content that appeared in the narratives of Władysław I the Elbow-high’s documents. References to the economic sphere occurring there were divided into two types. The first one contained information on the economic condition of an area, first and foremost about the destruction or war devastation that hit a given region or town. The second type justified ruler’s decisions, a desire to reform or to increase the benefits of the monarchy and his subjects. On the basis of the data obtained, an attempt was made to comment on the economic awareness of the ruler.